The Effect of Bacillus subtilis Bacteria Concentration on Production and Characterization of Pektinase Enzymes from Pineapple Peel Waste (Ananas comosus L. Merr) - Andre Agusta; Maria Marina Herawati (The University of Lampung, 2022)
This study aims to determine the effect of treatment concentrations (4%; 8%; 10%; 13%; 16%; 20%) of Bacillus subtilis bacterial isolates on the production of pectinase enzymes from pineapple peel waste, and the characteristics of the pectinase enzyme produced include (enzyme activity, optimum temperature, optimum pH, Km and Vmax values). The yield of crude enzyme extract production from the 6 treatments carried out, the highest yield was found in the 10% treatment at 1.59 g and the lowest in the 4% treatment at 1.53 g. In the results of enzyme characterization, the highest enzyme activity was found at a concentration of 20% at 1.883, and the pectinase enzyme produced was able to work optimally in environmental conditions with a temperature of 400C and pH 4 at all concentrations, but the highest activity at variations in temperature and pH was on enzymes with 20% bacterial concentration treatment, namely 0.680 at 400C and 0.650 at pH 4. Enzyme kinetics analysis obtained from the pectinase enzyme produced, showed the highest Km value of 0.021 at a concentration of 4% while the lowest value is 0.0095 at a concentration of 20%. Then at the Vmax value of the enzyme, the highest value was found at the 20% concentration treatment and the lowest value was at 4% treatment was 0.481.Keywords: Bacillus subtilis, Characterization, Enzyme Production, PektinaseEnzyme